Tail-tape-fused virion and non-virion RNA polymerases of a thermophilic virus with an extremely long tail - Anastasiia Chaban; Leonid Minakhin; Ekaterina Goldobina; Brain Bae; Yue Hao; Sergei Borukhov; Leena Putzeys; Maarten Boon; Florian Kabinger; Rob Lavigne; Kira S. Makarova; Eugene V. Koonin; et al. (Nature Communications, 2024)
Abstract Thermus thermophilus bacteriophage P23-45 encodes a giant 5,002-residue tail tape measure protein (TMP) that defines the length of its extraordinarily long tail. Here, we show that the N-terminal portion of P23-45 TMP is an unusual RNA polymerase (RNAP) homologous to cellular RNAPs. The TMP-fused virion RNAP transcribes pre-early phage genes, including a gene that encodes another, non-virion RNAP, that transcribes early and some middle phage genes. We report the crystal structures of both P23-45 RNAPs. The non-virion RNAP has a crab-claw-like architecture. By contrast, the virion RNAP adopts a unique flat structure without a clamp. Structure and sequence comparisons of the P23-45 RNAPs with other RNAPs suggest that, despite the extensive functional differences, the two P23-45 RNAPs originate from an ancient gene duplication in an ancestral phage. Our findings demonstrate striking adaptability of RNAPs that can be attained within a single virus species.